Efeito do enriquecimento ambiental na organização social do papagaio-verdadeiro (Amazona aestiva) mantido em cativeiro - Coppola, Milena Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Blue-fronted Amazon parrot is a monogamous species that has social intelligence. However, it is commonly a victim of environmental illegalities and of life in captivity. The goal of this study was to evaluate the social dynamics and behavioral repertoire when males and females of the same species were put together for the first time, with an emphasis on patterns that would validate the social bond between the birds and stereotypical behaviors. 13 captive males and 13 captive females were used, separated in isosexual groups during the first phase, in sexual groups during the second phase and isolated from the group, in pairs and as a couple, during the third phase. The observations were registered daily in the morning, with a recording time of 20 minutes/bird, adding up to 100 minutes of recording/bird/phase. The behavioral analysis were separated in 8 categories, always observing the maintenance of existing pairs and the new social formations when the birds were put together. For statistical analysis the Friedman test was used to compare the percentage of time that was spent doing each behavior between sexes and between phases, using significance values of P>0.05. The social composition in the isosexual phase was composed of 2 pairs of males, 2 pairs of females and three females. In the sexual phase there were 4 pairs of males and 3 pairs of isosexual females and 1 couple. The obtained results suggest that isolating Blue-fronted amazon parrots, even as a couple, does not promote a condition of animal well-being and maintenance of the social bond, as the stereotypical behaviors increased and the affiliative behaviors decreased in this condition. They also showed that the fidelity of the pairs was maintained in birds with dominant aspect, even in a new environmental and social condition

O papagaio verdadeiro é uma espécie monogâmica que possui inteligência social, porém, é comumente vítima das ilegalidades ambientais e da vida em cativeiro. O objetivo deste estudo foi avaliar a dinâmica social e o repertório comportamental ao juntar machos e fêmeas da espécie pela primeira vez; com enfoque nos padrões que validassem o vínculo social entre as aves e os comportamentos estereotipados. 13 machos e 13 fêmeas cativos foram utilizados; separados em grupos isossexuais na primeira fase, em grupo sexual na segunda fase e, isolados do grupo, aos pares e casal, na terceira fase. As observações foram registradas diariamente pela manhã, com tempo de filmagem de 20 minutos/ave, totalizando 100 minutos de registro/ave/fase. As análises comportamentais foram relacionadas em 8 categorias, sempre observando a manutenção de pares existentes e as novas formações sociais quando juntou-se as aves. Para análise estatística foi utilizado o teste de Friedman para comparar a porcentagem de tempo gasto em cada comportamento entre os sexos e entre as fases, com valor de significância adotado de P>0,05. A composição social na fase isossexual constitui-se de 2 pares de machos, 2 pares de fêmeas e um trio de fêmeas. Na fase sexual foram 4 pares de machos e 3 pares de fêmeas isossexuais e 1 casal. Os resultados obtidos sugerem que isolar papagaios verdadeiros, mesmo com seus pares, não promove uma condição de bem-estar animal e manutenção do vínculo social, uma vez que os comportamentos estereotipados aumentaram e os afiliativos diminuíram nesta condição. Também revelam que a fidelidade dos pares manteve-se em aves com aspecto dominante, mesmo em uma nova condição ambiental e social
Effect of environmental enrichement in the Social organization of the blue-fronted amazon parrot Kept in captivity (Amazona aestiva)
Keywords: Papagaio (Ave); Inteligência social; Animais - Proteção; Comportamento organizacional; Parrots; Animal welfare